Дослідження можливостей використання Assistants API для автоматизації процесу аналізу успішності учнів - Копєйчиков, І. Ю. (ХНУРЕ, 2024)
This work describes the concept of developing an information system module of a secondary education institution, namely a private lyceum, which aims to store and analyze the progress of students. The essence of this module is to collect and store information about the educational process, as well as a comprehensive analysis of learning results and the formation of a report on these results. To analyze the results of students' learning it was decided to use artificial intelligence tools, namely Assistants API from OpenAI. This will allow to provide students, their parents and teachers with up-to-date personalized reports on students' progress with conclusions about the learning process and recommendations for further learning and improvement of results.
Keywords: аналіз успішності учнів; Assistants API